Localization of putative transcription initiation site on the cloned rDNA fragment of Tetrahymena pyriformis. - Higashinakagawa, T (1981)
A DNA fragment (1.4 Kb) which codes for 5' region of 35S ribosomal precursor RNA (pre-rRNA) in Tetrahymena pyriformis was cloned with pBR322. The fragment was cleaved from the central part of the palindromic rDNA with restriction endonuclease KpnI and HindIII, and ligated to the larger moiety of pBR322 DNA-HindIII-BamHI fragment together with lambda DNA-KpnI-BamHI fragment through trimolecular ligation. The analysis of R-loop formed between KpnI-linearized recombinant plasmid and 35S pre-rRNA revealed a DNA:RNA hybrid region of 465 +/- 30 base pairs in length. Considering the contraction of DNA:RNA hybrids relative to DNA duplexes (Philippsen et al., J. Mol. Biol., 123, 387-404, 1978), the size of the hybrid region was corrected to about 490 base pairs. Alternatively, the size of DNA which was protected against nuclease S1 due to hybrid formation with 35S pre-rRNA was estimated to be 490 nucleotides long. These data indicate that the transcription initiation site is localized at about 490 base pairs from the HindIII site of the cloned rDNA fragment.